2015
DOI: 10.1080/07315724.2015.1009193
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofl-Alanyl-l-Glutamine Ingestion on One-Hour Run Performance

Abstract: Results indicated that ingestion of the alanine-glutamine dipeptide at either the low or high dose significantly improved time to exhaustion during high-intensity exercise compared to a no-hydration trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Time to exhaustion during the 90% of VO 2 max run was significantly longer during the LD and HD trials compared to DHY. These results though are reported elsewhere (McCormack et al, in press).…”
Section: Resultssupporting
confidence: 85%
“…Time to exhaustion during the 90% of VO 2 max run was significantly longer during the LD and HD trials compared to DHY. These results though are reported elsewhere (McCormack et al, in press).…”
Section: Resultssupporting
confidence: 85%
“…The same research group investigated the effects of L-alanyl-L-glutamine, either in low (1 g/500 mL) or high dose (2 g/500 mL), on physical performance during a basketball game (jump power, reaction time, shooting accuracy and fatigue), and observed an improvement in basketball shooting performance and visual reaction time with low dose of L-alanyl-L-glutamine compared to water ingestion (placebo) [41]. Similarly, McCormack et al [52] submitted endurance-trained men to a one-hour treadmill run at 75% of the VO 2peak followed by a run to exhaustion at 90% of the VO 2peak , after supplementing them with (i) L-alanyl-L-glutamine and a sports drink, (ii) only the sports drink (placebo) or (iii) without any supplementation (no hydration trial). The authors observed that plasma glutamine was higher and time to exhaustion was longer when supplementing with dipeptide compared to the no hydration trial, but there was no difference between L-alanyl-L-glutamine supplementation and the sports drink only (placebo).…”
Section: Glutamine and Its Anti-fatigue Propertiesmentioning
confidence: 99%
“…A 2016 study indicated that L-alanyl-L-glutamine maintained reaction time in an upper and lower-body activities after an exhaustive bout of treadmill running [ 526 ]. Finally, a 2015 paper determined that L-alanyl-L-glutamine significantly improved treadmill running performance when compared to no hydration [ 527 ]. Collectively this research indicates that L-alanyl-L-glutamine at dosages ranging 300–1000 mg per 500 mL of fluid can favorably influence hydration status and performance when compared to no fluid ingestion or water only ingestion.…”
Section: Introductionmentioning
confidence: 99%